Investigation of Business English Conversation Mastery by Indonesian Coffee and Cocoa Research Institute Employees in Jember - Indah Werdiningsih (EDUPEDIA, 2020)
The concept of English for Business purposes has endured substantial shifts over the last few years which caused by numbers of development, such as behaviour change of the customers, improvements in technology, and the coming together of Businesss Communication and English for Business Purposes. Due to this current situation, companies need to improve not only the quality of their product but also the quality of the human resources This research is intended to investigate the extent of Business Conversation mastery by ICCRI employees in 2019 and examine further the factors that may be related to it, such as (1) the teaching process carried out by teachers, and (2) the employees' perceptions of the importance of Business. Speaking test and a questionnaire is used to answer problems of the research.